2017
DOI: 10.1016/j.media.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Stereo vision-based tracking of soft tissue motion with application to online ablation control in laser microsurgery

Abstract: Recent research has revealed that image-based methods can enhance accuracy and safety in laser microsurgery. In this study, non-rigid tracking using surgical stereo imaging and its application to laser ablation is discussed. A recently developed motion estimation framework based on piecewise affine deformation modeling is extended by a mesh refinement step and considering texture information. This compensates for tracking inaccuracies potentially caused by inconsistent feature matches or drift. To facilitate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It has been shown that an ensemble of ErfNet and UNet yielded the most successful results on segmenting endoscopic image data. Schoob et al [30] reported that image-based online control of incision lasers for soft tissue undergoing motion is feasible with an imaging pipeline running at 73.5 Hz. Therefore, both ENet and ErfNet are well-suited in terms of efficiency for later use in autonomous or robot aided interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that an ensemble of ErfNet and UNet yielded the most successful results on segmenting endoscopic image data. Schoob et al [30] reported that image-based online control of incision lasers for soft tissue undergoing motion is feasible with an imaging pipeline running at 73.5 Hz. Therefore, both ENet and ErfNet are well-suited in terms of efficiency for later use in autonomous or robot aided interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this system was integrated into the controller of a new robotic endoscope for non-contact FIGURE 12 | Real-time stereoscopic methods for (A) 3D reconstruction (Schoob et al, 2015). (B) intraoperative incision planning and visualization (Schoob et al, 2017), and (C) laser focus adjustment (Schoob et al, 2016 endolaryngeal laser surgery, enabling novel visualization concepts for eye-in-hand laser manipulation, as demonstrated in a user study with novice and expert users (Kundrat et al, 2020).…”
Section: Surgical Ar For Endoscopic Laser Microsurgery Beyond µRalpmentioning
confidence: 99%
“… Real-time stereoscopic methods for (A) 3D reconstruction ( Schoob et al, 2015 ). (B) intraoperative incision planning and visualization ( Schoob et al, 2017 ), and (C) laser focus adjustment ( Schoob et al, 2016 ). …”
Section: Micro-technologies and Systems For Robot-assisted Endoscopic Laser Microsurgerymentioning
confidence: 99%
“…25 Estimation of scene motion and deformation is implemented with a tracking algorithm that is optimised for soft tissues with errors of less than 0.1 mm. 26 The robotic eye-inhand setup with rigid laser optics integrated to the tip causes endoscopic visualisation with scene motion while displacing the laser spot. This is different from familiar scenarios in transoral laser surgery, where the beam is displaced on a static scene in the microscopic view.…”
Section: Robotic Frameworkmentioning
confidence: 99%